Development of Competency Manual for the Philippine Coast Guard (PCG) Commanding Officers - Berbie, Aries C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study emphasized the importance for effective leadership in the Philippine Coast Guard (PCG) and introduces the development of a specialized Competency Manual tailored for PCG Commanding Officers, guided by the Dreyfus model of skills acquisition. While effective leadership is vital for maritime safety and security, the absence of a structured competency framework poses challenges for PCG Commanding Officers, impeding their adaptability and effectiveness in rapidly evolving maritime environment. The development process encompassed a thorough needs assessment, which included reviewing PCG regulations, competency frameworks, and conducting a comprehensive analysis of the Dreyfus model. Collaborative efforts with subject matter experts, surveys, and pilot testing involving PCG officers played a pivotal role in refining the content of the manual. The result of the study yields a Competency Manual that meticulously defines specific competencies, knowledge, skills, and behaviors deemed essential at each stage of the Dreyfus model. Covering critical areas such as maritime regulations, navigation, decision-making, leadership, and crisis management, the manual precisely caters to the unique demands placed on PCG Commanding Officers. The Competency Manual stands out as a structured and progressive tool for skill development, ensuring that PCG Commanding Officers are well-prepared to navigate the difficult challenges inherent in their roles. Effective implementation that entails the seamless integration of the manual into PCG's training programs, conducting routine assessments, and establishing channels for continuous improvement. This strategic approach seeks to foster the development of PCG Commanding Officers into highly proficient leaders, empowering them to adeptly protect maritime interests in the Philippines.